2021
DOI: 10.1007/s11356-021-14544-8
|View full text |Cite
|
Sign up to set email alerts
|

The photocatalytic rate of ZnO supported onto natural zeolite nanoparticles in the photodegradation of an aromatic amine

Abstract: The ZnO supported on the ball-mill prepared clinoptilolite nanoparticles (CNPs) was prepared via an ionexchange process followed by the calcination process. The ZnO-CNP catalyst was brie y characterized by XRD, FTIR, and DRS techniques. The pHpzc value for the various ZnO-CNPs was about 7.1 that no changed with the ZnO loading. By applying the Scherrer equation on the XRD results, a nano-dimension was obtained for the catalyst. Band gap energy of the ZnO-CNP samples were estimated by applying the Kubelka-Munk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…For example, the dispersion of Pt nanoparticles into mesoporous Co 3 O 4 was reported to increase the catalytic oxidative degradation efficiency toward methylene blue (MB) dye, with almost 100% removal after 60 min of treatment [ 64 , 65 ]. Similar results were recorded from supported ZnO nanoparticles using zeolite [ 66 , 67 ], supported iron nanoparticles using zeolite [ 68 , 69 ], and supported Au nanoparticles into TiO 2 and BiVO 4 [ 70 , 71 ]. Microporous and mesoporous solids were employed for supporting metal and metal oxide nanoparticles; some of them are noted to be low-cost supports such as zeolite, silica, graphene, carbon, C 3 N 4 , and clay minerals [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Metal and Metal Oxide Nanoparticles In Aopssupporting
confidence: 73%
“…For example, the dispersion of Pt nanoparticles into mesoporous Co 3 O 4 was reported to increase the catalytic oxidative degradation efficiency toward methylene blue (MB) dye, with almost 100% removal after 60 min of treatment [ 64 , 65 ]. Similar results were recorded from supported ZnO nanoparticles using zeolite [ 66 , 67 ], supported iron nanoparticles using zeolite [ 68 , 69 ], and supported Au nanoparticles into TiO 2 and BiVO 4 [ 70 , 71 ]. Microporous and mesoporous solids were employed for supporting metal and metal oxide nanoparticles; some of them are noted to be low-cost supports such as zeolite, silica, graphene, carbon, C 3 N 4 , and clay minerals [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Metal and Metal Oxide Nanoparticles In Aopssupporting
confidence: 73%
“…UV-vis spectroscopy was used to monitor the degradation extent of the MA/CAN mixture pollutants, and the chemical oxygen demand (COD) was used to estimate the mineralization of the mixtures. Since ZnO can absorb a larger range of the light spectrum than TiO 2 , researchers investigated the photocatalysis properties of ZnO/CP in different kinds of wastewater, such as bromothymol blue [81], phenylhydrazine [59], 4-nitrophenol [82], and aromatic amine [83] aqueous solutions. Mohammadzadeh et al [84] prepared the ZnO/CP composites by mixing the Zn(NO 3 ) 2 solution and CP powder.…”
Section: Common Semiconductor/clinoptilolite Photocatalystsmentioning
confidence: 99%
“…This result indicates a positive surface charge under the conditions studied and agrees well with pH PZC values reported in previous studies. 72–74…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates a positive surface charge under the conditions studied and agrees well with pH PZC values reported in previous studies. [72][73][74] Regarding the change in the sorption capacity of nanoparticles over time (Fig. 3c), it was observed that biogenic CuO NPs reach saturation aer 180 minutes of sorption, while ZnO NPs reach saturation later, aer 240 minutes.…”
Section: Study Of Lead(ii) Ion Sorption Kineticsmentioning
confidence: 96%